Butterfly diversity and abundance with reference to habitat heterogeneity in and around Neora Valley National Park, West Bengal, India - Roy, Utpal Singha; Mukherjee, Mayukh; Mukhopadhyay, S. K. (Our Nature, 2013)
Butterfly diversity in and around Neora Valley National Park (NVNP), West Bengal, India was studied from three different habitat types that included thick vegetation assemblage with closed canopy cover, edges of forest and areas of human intervention during April – May 2010. A total of 30 butterfly species belonging to the families of Hespeririidae (3.33%), Papilionidae (16.65%), Pieriidae (13.32%), Nymphalidae (53.28%) and Lycaenidae (13.32%) were identified in the present investigation. Highest butterfly diversity and abundance was recorded from areas of forest edges (54.83% of individuals represented by 16 different species), while dense forest (30.64 % of individuals represented by 11 different species) and areas with human habitats (14.52 % of individuals represented by 8 different species) showed lower butterfly diversity and abundance. Accordingly highest Shannon Weiner diversity score of 2.32 was recorded from areas of forest edges. The butterflies that showed high occurrences were Indian Tortoise Shell (Aglais cashmiriensis), Yellow Coster (Acraea issoria) and Himalayan Five Ring (Ypthima sakra). Only 1 butterfly species, Yellow Coster (A. issoria) was found to co-occur in all the three sites. Accelerating human civilizations has lead to destruction of much of the global natural habitats while it has often been found to exert adverse effects on biodiversity. Findings made during this study also indicate negative influence of anthropogenic intervention on overall butterfly diversity from the present location. DOI: http://dx.doi.org/10.3126/on.v10i1.7751